Brief report: Poor self‐regulation as a predictor of individual differences in adaptive functioning in young children with autism spectrum disorder. Issue 8 (6th April 2018) - Uljarević, Mirko; Hedley, Darren; Nevill, Rose; Evans, David W.; Cai, Ru Ying; Butter, Eric; Mulick, James A.
Abstract : The present study examined the link between poor self‐regulation (measured by the child behavior checklist dysregulated profile [DP]) and core autism symptoms, as well as with developmental level, in a sample of 107 children with autism spectrum disorder (ASD) aged 19–46 months. We further examined the utility of DP in predicting individual differences in adaptive functioning, relative to the influence of ASD severity, chronological age (CA), and developmental level. Poor self‐regulation was unrelated to CA, developmental level, and severity of ADOS‐2 restricted and repetitive behaviors, but was associated with lower ADOS‐2 social affect severity. Hierarchical regression identified poor self‐regulation as a unique independent predictor of adaptive behavior, with more severe dysregulation predicting poorer adaptive functioning. Results highlight the importance of early identification of deficits in self‐regulation, and more specifically, of the utility of DP, when designing individually tailored treatments for young children with ASD. Autism Res 2018, 11: 1157–1165 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study explored the relationship between poor self‐regulation and age, verbal and non‐verbal developmental level, severity of autism symptoms and adaptive functioning in 107 children with autism under 4 years of age. Poor self‐regulation was unrelated to age, developmental level, and severity of restricted and repetitive behaviors but was associated with lower social affect severity. Importantly, more severe self‐regulation deficits predicted poorer adaptive functioning.